Biochemical Basis and Therapeutic Implications of Angiogenesis - Mehta, Jawahar L.; Dhalla, Naranjan S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Angiogenesis plays a key role in human physiology and pathophysiology. While necessary for tissue growth and development, uncontrolled angiogenesis plays a role in the progression of certain tumors as well as atherosclerosis. Lack of angiogenesis may be the basis of myocardial ischemia and stroke. Knowledge on the mechanisms of angiogenesis is growing very rapidly, and may lead to important drugs for therapy of a variety of clinical disorders. Experts from around the world have contributed a vast array of data on different aspects of angiogenesis in this volume edited by Professors Mehta and Dhalla. This information will be of immense help to basic scientists, clinicians and those involved in drug development.
Part A: Molecular Mechanisms of Angiogenesis -- Endothelial Growth Factor Receptors in Angiogenesis -- Role of Transforming Growth Factor Beta in Angiogenesis -- Role of Cytokines in Angiogenesis: Turning it On and Off -- Neuropeptides in Angiogenesis -- The Role of Integrins in Angiogenesis -- Regulation of Angiogenesis by Hypoxia-inducible Factors -- Role of Mast Cells in Angiogenesis -- Vascular Stem Cells in Regulation of Angiogenesis -- Toll-like Receptor-linked Signal Transduction in Angiogenesis -- The Role of Sex Steroids in Angiogenesis -- Biochemical Mechanisms of Exercise-induced Angiogenesis -- Part B: Pathophysiological Aspects of Angiogenesis -- Angiogenesis in Atherosclerosis: An Overview -- Role of Serotonin in Angiogenesis in Diabetes -- Brain Angiogenesis after Stroke -- Angiogenesis in Myocardial Ischemia -- Adipose Tissue-derived Mesenchymal Stem Cell and Angiogenesis in Ischemic Heart Disease -- Trials of Angiogenesis Therapy in Patients with ischemic Heart Disease -- Angiogenesis in Cancer -- Potential Mechanisms Linking Oxidized LDL to Susceptibility to Cancer -- Role of Genetic Polymorphisms in the Angiogenesis Pathway and Non-small Cell Lung Cancer Tumor Behavior -- Part C: Pharmacology and Therapy of Angiogenesis -- Angiogenesis and Arteriogenesis Factors: Their Role in the Treatment of Cancer and Arterial Regeneration -- Physiological Roles and Therapeutic Implications of Hepatocyte Growth Factor for Angiogenesis -- Harnessing Endothelial Progenitor Cells for Therapeutic Angiogenesis -- Microarray and MiRs in Angiogenesis -- MicroRNA and Cardiovascular Disorders, with a Focus on Angiogenesis -- An Overview of Angiogenesis Inhibitors from Natural Sources -- Index.
Keywords: Medicine; Oncology; Human physiology; Cardiology; Cell receptors; Stem cells; Biomedicine; Human Physiology; Cardiology; Cancer Research; Receptors; Molecular Medicine; Stem Cells